Epilepsy treatment in neuro-oncology: A rationale for drug choice in common clinical scenarios - Sánchez-Villalobos, José Manuel; Aledo-Serrano, Ángel; Villegas-Martínez, Irene; Shaikh, Mohd Farooq; Alcaraz, Miguel (Frontiers in Pharmacology, 2022)
Epilepsy represents a challenge in the management of patients with brain tumors. Epileptic seizures are one of the most frequent comorbidities in neuro-oncology and may be the debut symptom of a brain tumor or a complication during its evolution. Epileptogenic mechanisms of brain tumors are not yet fully elucidated, although new factors related to the underlying pathophysiological process with possible treatment implications have been described. In recent years, the development of new anti-seizure medications (ASM), with better pharmacokinetic profiles and fewer side effects, has become a paradigm shift in many clinical scenarios in neuro-oncology, being able, for instance, to adapt epilepsy treatment to specific features of each patient. This is crucial in several situations, such as patients with cognitive/psychiatric comorbidity, pregnancy, or advanced age, among others. In this narrative review, we provide a rationale for decision-making in ASM choice for neuro-oncologic patients, highlighting the strengths and weaknesses of each drug. In addition, according to current literature evidence, we try to answer some of the most frequent questions that arise in daily clinical practice in patients with epilepsy related to brain tumors, such as, which patients are the best candidates for ASM and when to start it, what is the best treatment option for each patient, and what are the major pitfalls to be aware of during follow-up.